Development of Madrasah Curriculum in Indonesia - Muhammad Zaid; Muharrir Na'iem; Andi Fitriani Djollong; Nur Aisyah Ustar; Muminayah (Universitas Muhammadiyah Palu, 2025)
National education and is considered a newcomer who is considered to have many problems in terms of quality, management and curriculum. The madrasah curriculum continues to be perfected by referring to the development of the times and the needs of the community. Decree of the Minister of Religion No. 184 of 2019 emphasizes the importance of religious moderation, character education, and local content in the madrasah curriculum. With this policy, it is hoped that madrasas can innovate in the implementation of the curriculum, so that graduates have strong religious knowledge and good skills and character to face global challenges.